Necrotizing pulmonary aspergillosis and ventricular assist device infection: case report and review of literature. Issue 5 (26th September 2015) - Kornberger, A.; Walter, V.; Jaeger, F.; Lehnert, T.; Soriano, M.; Moritz, A.; Stock, U.A.; Beiras‐Fernandez, A.
Abstract Necrotizing pulmonary aspergillosis and Aspergillus device infection are rare and have potentially fatal complications after left ventricular assist device (LVAD) implantation. To date, few cases of patients surviving Aspergillus device infection have been published, with survival reported only after device removal. We present a patient implanted with an LVAD in whom necrotizing pulmonary aspergillosis with device involvement was successfully treated by segmentectomy and prolonged antifungal treatment without device exchange or removal. Similar cases in the literature were searched for and are discussed in view of the severity of this complication.